A EFEKTIFITAS PENDEKATAN BEHAVIORISTIK DENGAN TEHNIK MODELING UNTUK MEMBANGUN PRIBADI ENDURANCE DAN PRIBADI HETEROSEXUALITY : EFEKTIFITAS PENDEKATAN BEHAVIORISTIK DENGAN TEHNIK MODELING UNTUK MEMBANGUN PRIBADI ENDURANCE DAN PRIBADI HETEROSEXUALITY - Dharsana, I Ketut; Ida Ayu, Prahasti Negari (Jurnal IKA, 2025)
Personal endurance is very important as it encourages students to have the need to be able to survive to overcome all obstacles and obstacles in achieving the expected goals. Personal heterosexuality is the need for sexual relations with other people, including associating with the opposite sex, having affection for the opposite sex, having a sense of concern for the opposite sex. Behavioral is an adaptation of the behavioristic counseling school, which emphasizes attention to visible behavior. Modeling is a learning process through observation after observing the behavior of other people. The aim of this research is to determine the effectiveness of the Behavioristic approach with modeling techniques to build personal endurance and personal heterosexuality in class VIII students of SMP Negeri 2 Denpasar. This research design uses a one group pretest-posttest design with a research population of all students in grades VIII.1, VIII.2 and VIII.3, totaling 90 people. Sampling used random sampling and random class techniques as an intact group. Based on the selection results, classes VIII.2 and VIII.3 were obtained as the assessment sample. Statistical tests use the t-test to determine the effectiveness of the treatment that has been carried out. H0 is rejected if tcount > ttable. H0 is accepted if tcount ≤ ttable. Based on the H1 ttest, the tcount was 4.926, while the ttable with db N-1 = 30 – 1 = 29 and a significance level of 5% (0.05) was 1.699. Based on the H2 t-test, the tcount was 3.738, while the ttable with db N-1 = 30 – 1 = 29 and a significance level of 5% (0.05) was 1.699. Because tcount > ttable it can be concluded that H0 is rejected, H1 and H2 are accepted..